2020
DOI: 10.3390/min10060528
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of 3D-Shape Preferred Orientation (SPO) Using Synchrotron μ-CT: Applications for Estimation of Fault Motion Sense in a Fault Gouge

Abstract: We propose a 3D-shape preferred orientation (SPO) measurement method of rigid grains using synchrotron micro-computational tomography (μ-CT). The method includes oriented sampling, 3D μ-CT imaging, image filtering, ellipsoid fitting, and SPO measurement. After CT imaging, all processes are computerized, and the directions of thousands of rigid grains in 3D-space can be automatically measured. This method is optimized for estimating the orientation of the silt-sized rigid grains in fault gouge, which indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
0
9
0
2
Order By: Relevance
“…In addition, as a result of measuring the SPO of the fault gouge and breccia quartz grains, it was confirmed that this alignment was also exhibited in natural fault rock samples [11]. Recently, the fault motion was estimated by measuring the SPO of the major axis of the grain in 3D through a CT image of the fault gouge [13,14]. According to previous studies, the densest points of the SPO are aligned in the P-shear direction; therefore, the fault motion direction can be estimated from the SPO.…”
Section: Orientation Of Major Axismentioning
confidence: 57%
See 4 more Smart Citations
“…In addition, as a result of measuring the SPO of the fault gouge and breccia quartz grains, it was confirmed that this alignment was also exhibited in natural fault rock samples [11]. Recently, the fault motion was estimated by measuring the SPO of the major axis of the grain in 3D through a CT image of the fault gouge [13,14]. According to previous studies, the densest points of the SPO are aligned in the P-shear direction; therefore, the fault motion direction can be estimated from the SPO.…”
Section: Orientation Of Major Axismentioning
confidence: 57%
“…The method of measuring 3D-SPO of the collected sample was based on Sim et al (2020) [14]. Octopus 8.9 software (XRE, Gent, Belgium) was used for image reconstruction and all image-related processes were performed using Amira 6.5 (Thermo Fisher Scientific, Hillsboro, OR, USA) and MATLAB (MathWorks, Natick, MA, USA).…”
Section: Shape Preferred Orientation Measurement Methodsmentioning
confidence: 99%
See 3 more Smart Citations